Leadership in Action : a Question of Leadership - Is Leadership More Art or More a Science? - Cartwright, Talula (Center for Creative Leadership, 2004)
Leadership, however, has traditionallybeen viewed as an art, but the notion that leadership can also be a science deserves a closer look.